A Race Against Time—Changing the Natural History of CRIM Negative Infantile Pompe Disease - Gupta, Punita; Shayota, Brian J.; Desai, Ankit K.; Kiblawi, Fuad; Myridakis, Dorothy; Messina, John; Tah, Peter; Tambini-King, Lorien; Kishnani, Priya S. (Frontiers in Immunology, 2020)
We report the clinical course of the first prenatally diagnosed cross-reactive immunologic material (CRIM)-negative infantile Pompe disease (IPD) patient [homozygous for c.2560C>T (p.Arg854X) variant in the GAA gene] to undergo prophylactic immune tolerance induction (ITI) and enzyme replacement therapy (ERT) within the first two days of life. Both parents were found to be carriers of the c.2560C>T (p.Arg854X) variant through prenatal carrier screening. Fetal echocardiogram at 31 weeks of gestation showed left ventricular hypertrophy. An echocardiogram on the first day of life revealed marked biventricular hypertrophy. Physical exam was significant for macroglossia and hypotonia. A short course of Prophylactic ITI with rituximab, methotrexate, and intravenous immunoglobulin (IVIG) in conjunction with ERT at a dose of 20 mg/kg every other week was started on day 2 of life. The patient completed the ITI protocol safely and complete B-cell recovery, based on CD19 count, was noted by 3 months of age. The patient never developed anti-rhGAA IgG antibodies to ERT. Vaccinations were initiated at 9 months of age, with adequate response noted. Complete recovery of cardiac function and left ventricular mass was seen by 11 weeks of age. At 8 months of age, the patient developmentally measured at 75-90% on the Alberta Infant Motor Scale, walked at 11 months and continues to develop age-appropriately at 50 months of age based on the Early Learning Accomplishment Profile. ERT dosing was increased to 40 mg/kg every 2 weeks at 32 months of age and frequency increased to 40 mg/kg every week at 47 months of age. Patient continues to have undetectable antibody titers, most recently at age 50 months and urine Hex4 has remained normal. To our knowledge, this is the first report of successful early ERT and ITI in a prenatally diagnosed CRIM-negative IPD patient and the youngest IPD patient to receive ITI safely. With the addition of Pompe disease to the Recommended Uniform Screening Panel(RUSP) and its addition to multiple state newborn screening programs, our case highlights the benefits of early diagnosis and timely initiation of treatment in babies with Pompe disease, who represent the most severe end of the disease spectrum.